INTRODUCTION AND TRAINING: THE SYNERGY OF AQUACULTURE AND HYDROPONICS (BUDIKDAMBER) WITH FOURTH GRADE STUDENTS AT LABORATORY PRIMARY SCHOOL UM AS A MANIFESTATION OF P5 IN ELEMENTARY EDUCATION CONTEXTS - Priyanti, Novie Ary; Habiburrahman, Novan; Lidiastuti, Arinda Eka; Fatimah, Siti; Nisa’, Liza Choirun; Muttaqin, Muhammad Zainul; Hariva, Zayyana (Jurnal Abdi Negeriku, 2024)
This activity aims to introduce and train 4th grade students of SD Laboratorium UM on the principles of harmony between aquaculture and simple hydroponics by utilizing the Budikdamber method. This initiative is embedded in the Pancasila Student Profile Strengthening Project (P5), which combines practical and theoretical approaches to learning. During the implementation, students were involved in designing, constructing, maintaining, and cultivating the output of the Budikdamber system, which consists of catfish aquaculture and hydroponic kale plants that mutually support a balanced ecosystem cycle. The results of this training showed an increase in students' knowledge and skills in sustainable agriculture, along with creative and innovative cultivation practices. In addition, it fosters a sense of environmental responsibility among students. The program is expected to be a model for P5 that blends theory and practice, equipping students with relevant skills for the future. The outputs of this activity include publications in accredited national journals and news articles in online media. We also hope that our partners can directly benefit from the knowledge gained through this training.